Differential effects of hand and mouth gesture training on L2 English pronunciation: targeting suprasegmental and segmental features - Yamane, Noriko; Shinya, Masahiro; Tan, Xiaofeng; Chiya, Amos (Frontiers in Communication, 2026)
Human communication inherently integrates speech and gesture. Acquiring second language (L2) pronunciation, encompassing both segmental (e.g., vowels) and suprasegmental features (e.g., rhythm, fluency), remains a major challenge. This study investigated how two types of gesture training—manual (hand gesture training) versus articulatory (mouth gesture training)—influence these features in Japanese EFL learners. Forty university students participated in a four-week counterbalanced design, receiving hand gesture training (rhythmic circular motions) and mouth gesture training (bio-visual feedback for /æ/ vs. /ʌ/ distinction). Speech rate (as a suprasegmental proxy) and second formant (F2) values of target vowels (as a segmental proxy) were measured at pre, mid-, and post-training. Results revealed distinct effects: hand gesture training significantly improved speech rate across both groups, enhancing suprasegmental fluency, while mouth gesture training significantly improved F2 distinction for /æ/. These findings suggest that hand and mouth gestures target complementary aspects of L2 pronunciation. Taken together, the results support an embodied, multimodal approach to pronunciation instruction, highlighting the pedagogical value of integrating suprasegmental fluency practice with segmental refinement.